A adoção do comércio eletrônico em relação aos estágios de informatização: um estudo no setor metal-mecânico brasileiro - Boehs, Carlos Gabriel Eggert; Abib, Gustavo; Mazo, Miriam Stolses (Revista Gestão da Produção Operações e Sistemas, 2006)
The adoption of the information technology for new forms in the sales process is a reality. Itsapplication carries strong advantages to be utilized by the companies, such as cost reduction, process agility andelimination of the intermediation. Connected with these arguments, the utilization of the e-commerce dependson the companies’ capacity to manage efficiently the assets and information technologies. The adoption of ecommercepractices in the Metal-Mechanic industry is the main purpose of this study, which had thecollaboration of 174 small, medium and large Brazilian companies. The analyses of the results indicated arelation between the level of information technology (I.T.) adoption and the use of e-commerce, showing thatthe accumulated experience at the management of I.T. has a positive influence in e-commerce practices. Otheranalyzed data showed that small and large companies have a higher level of e-commerce practices. The studyalso verified that in companies of this segment the use of e-commerce is becoming more and more important,in addition to the traditional sales processes.Keywords: E-commerce; Information Technology; Sales Process.